Establishing a novel partnership model to deploy health services for children with autism in a low-resource setting - experience from Sri Lanka - Bhavana Sivayokan; Sambasivamoorthy Sivayokan; Thirunavukarasu Kumanan; Gitanjali Sathiadas; Nadarajah Sreeharan (Elsevier, 2023)
Summary: Sri Lanka is representative of challenges faced by low-income and middle-income countries, including the rise in the prevalence of autism and the lack of sufficient autism-specific services in the state sectors. The experience in establishing a Center to provide services for children with autism in Northern Sri Lanka is described. Funding and resourcing were accessed through an innovative partnership-based public/non-governmental organisation/charity model, where service-based outcomes were the main objectives. This model, incorporating state institutions, local and international charity organisations, and volunteers, devised a bespoke approach to care provision using the available resources under the clinical supervision of a consultant psychiatrist and the administrative purview of the Regional Director of Health Services. The evolution of this Center into a Learning Health System is described, reflecting how a minimalistic partnership approach focused on the integration of existing organisations and services could be a feasible model for the delivery of high-quality healthcare in low-resource settings.